Valores romanos y ejes transversales - García de Paso Carrasco, María Dolores (Estudios clásicos, 1999)
The paper deals with the values of Roman society which had an influence on the future. This values are individual and social. Humanitas is presented as a summary of values. This is referred to the didactic of Classical Culture in secondary schools.